Production of Instant Noodles with The Addition of Catfish Bone (Pangasius sp.) - Panjaitan, Pola S.T.; Tanjung, Anasri; Sopha, Detia (PELAGICUS, 2023)
Processing of catfish in general will produce by-products, mostly heads, viscera, skin, spines, and bones. This study aimed to determine the preference level after the addition of catfish bones (Pangasius sp.) to instant noodles by using a hedonic test and to determine the chemical quality of instant noodles with the addition of catfish bones (Pangasius sp) such as water content, protein content, and calcium The process of making instant noodles was carried out with four treatments of fish bones addition as follows 7%, 10%, and 13%. The processing steps of making instant noodles with the addition of catfish bones begin with receiving raw materials, washing the bones, steaming the bones, smoothing the bones, mixing the dough with the addition of catfish bone, grinding, molding, steaming, slicing and frying. The results of the chemical quality test for water content met Indonesian National Standards SNI 3551-2012 concerning "Instant Noodles" for F1 of 7.52%. The protein content in the F1, F2, and F3 formulations complied with the Indonesian National Standards SNI 3551-2012, and the calcium levels in the catfish bone instant noodles (Pangasius sp.) were able to meet the calcium levels in the F1 356.78, F2 416.81 and F3 565.03. The best formulation of instant noodles with the addition of catfish bones (Pangasius sp.) was obtained in the F3 formulation (13%).